BIOAKUMULASI MERKURI DAN STRUKTUR KOMUNITAS GASTROPODA DI KAWASAN BEKAS PENGGELONDONGAN EMAS TRADISIONAL, MUARA SUNGAI LAMPON, BANYUWANGI, JAWA TIMUR - , SUSINTOWATI, Dr. Suwarno Hadisusanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Tradistional gold mining at Lampon Banyuwangi district was used mercury amalgamation. Tailings are discharged to waters, that caused mercury pollution. Mercury accumulation can be trace in sediments and benthic organisms such as Gastropods. Although the gold mining has been ceased, the impact of mercury pollution can be traced. This research were aimed to determine the mercury concentration in sediments, determine mercury bioaccumulation in Gastropodâs soft body part, to understand the Gastropods hepatopancreas structure and to understand the community structure in former traditional gold mining Lampon estuary, Banyuwangi. Study site administratively located at Banyuwangi district East Java. The research began in August 2011 until May 2012. The methods of data collection is purpossive random sampling at 3 sites. Mercury analysis using SNI 06.6992.2-2004 methods and than reads by Mercury Analyzer at LPPT UGM Yogyakarta. Hepatopancreas structure of Terebralia sulcata and Nerita argus was preparating with paraffin methods and Hematoxilin Ehrlichâs-Eosin staining method. Accumulation of mercury in the tailings about 137.54 ppm, in sedimens of site I to 0.45 ppm, in sedimens of site II to 65.52 ppm, 1.17 ppm in sediments of site III and in the tailing piles remainings after the mining ceased to 634.19 ppm. Bioaccumulation in Terebralia sulcata 3.10 ppm, Nerita argus to 3.03 ppm and in Patella intermedia 0.44 ppm. The values of mercury accumulation are very high at all. Residual vesicles are found in hepatopancreas of Terebralia sulcata at site I. The residual vesicles are the sign of mercury detoxification proccess. Vesicles are thougt contain inclutions of residual electrons and methallothionine compaction as a result of mercury ions detoxification by hepatopancreas cells. The hepatopancreas tubulus of Nerita argus undergo disintegration and severe athropy. Clumped patterns of the Gastropods distribution are thought to allegedly in response to external factors including mercury pollution and the other resources. The diversity index were in low value, its mean domination by a single species at each site. Nerita argus is the once of the dominating species. Although the accumulation of mercury is high enough and disintegrated hepatopancreas experienced, severe athropy, Nerita argus still exist in this mining region. The gold mining at Lampon is the small gold mining and has been ceased but the pathological effects of mercury pollution on aquatic organisms, espesially Gastropods is very significant.